A discourse analysis of fundraising letters in English and Vietnamese - Trịnh, Thị Hồng Vân; Nguyễn Thị Quỳnh Hoa (ĐHĐN : ĐHĐN., 2015)
Fundraising is largely a persuasive activity that seeks to convince donors to contribute to a worthy cause. Based on the theories of discourse analysis, this thesis conducts a discourse analysis of English and Vietnamese fundraising letters in order to discover some typical discourse features and then find out the similarities and differences between fundraising letters in English and Vietnamese in terms of the layout, persuasive strategies and cohesive devices. Forty samples of English fundraising letters (EFLs) and fourth samples of Vietnamese fundraising letters (VFLs) were collected in both the form of direct mails and online mails which conform to the format of a formal letter. After describing, classifying and analyzing the layout, persuasive strategies and cohesive devices of fundraising letters in English and Vietnamese, we compare and contrast the above linguistic aspects to find out the similarities and differences between the two languages. In terms of the layout, EFLs and VFLs consist of seven structural elements to construct the format of a formal letters and seven moves: 1) get attention, 2) introduce the cause and/or establish credentials of organization, 3) solicit response, 4) offer incentive, 5) reference insert, 6) express gratitude, and 7) conclude with pleasantries which based on ―Discourse on the move‖ (Biber et al 2007). With the regard to persuasive strategies, the study analyses the three appeal categories of Aristotelian persuasion: rational (logos), credibility (ethos) and affective/emotional (pathos) developed by Connor and Gladkov (2004). For the cohesive devices, the thesis studies both lexical cohesion and grammatical cohesion. It is hoped that the results of this study can be helpful for teachers, learners of English as well as letter writing practitioners.
Master thesis in social sciences and humanities.
Keywords: discourse analysis of fundraising letters in English and Vietnamese; discourse analysis -- fundraising letters